Regulation of hydrophilicity/hydrophobicity of aluminosilicate zeolites: a review. Issue 4 (4th July 2021) - Wang, Cheng; Guo, Huidong; Leng, Shaozheng; Yu, Jiale; Feng, Kai; Cao, Liyun; Huang, Jianfeng
Abstract: The hydrophilicity/hydrophobicity of zeolites has been received increasing attentions due to its great influence on the physical, chemical property and application of zeolites. Generally, zeolites with different hydrophilicity/hydrophobicity exhibit different interaction with molecules/contaminations of different polarity, and thus have found promising applications in various and different fields. In this review, we first discuss the two main influence factors, i.e. SiO2 /Al2 O3 ratio and surface hydroxyl groups affecting hydrophilicity/hydrophobicity of aluminosilicate zeolites. Then, we give an overview of the ways for regulation of hydrophilicity/hydrophobicity of zeolites, i.e. hydrothermal synthesis, post synthesis for SiO2 /Al2 O3 ratio regulation and heat treatment, surface modification, water intrusion-extrusion method for hydroxyl groups regulation. The third, the hydrophilicity/hydrophobicity determination methods, i.e. water vapor adsorption, hydrocarbon/water vapor adsorption and TG experiment methods are concluded and compared. Finally, the problems and challenges for the future of this subject are discussed.